Artificial Intelligence: Applications and Reflections [In Arabic] - Boubaha, Souad (Finance and Business Economies Review, 2022)
Artificial intelligence is the main important result of the Fourth Industrial Revolution because of its multiple uses in many fields such as industry, economy, technology and education. It should also allow opportunity to unlimited innovations and lead to more industrial revolutions, bringing about a fundamental change in human life. Therefore, this research paper aims to shed light on artificial intelligence as one of the most important fields in the modern period and demonstrate its most applications and various consequences. To achieve this, the descriptive approach was followed to identify the concepts associated with artificial intelligence, as well as the identification of its main important effects, in addition to the analytical approach to analyse the most important reflections of artificial intelligence techniques. This study concluded that the use of artificial intelligence applications in many fields has become an undeniable fundamental role in our world today. and that we must prepare to enter the Fourth Industrial Revolution by investing in human and artificial intelligence. Even though the science of artificial intelligence remains a vast field, many of its theories are still being researched and developed.